2023
DOI: 10.3390/biomedicines11102731
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral Edema in Gliomas: A Review of Mechanisms and Management

Kazufumi Ohmura,
Hiroyuki Tomita,
Akira Hara

Abstract: Treating malignant glioma is challenging owing to its highly invasive potential in healthy brain tissue and the formation of intense surrounding edema. Peritumoral edema in gliomas can lead to severe symptoms including neurological dysfunction and brain herniation. For the past 50 years, the standard treatment for peritumoral edema has been steroid therapy. However, the discovery of cerebral lymphatic vessels a decade ago prompted a re-evaluation of the mechanisms involved in brain fluid regulation and the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…New therapeutic strategies targeting BD and the MLV functions appear to be promising [16][17][18]. The re-discovery of MLVs prompted a re-evaluation of the mechanisms responsible for regulation of BD and the formation of cerebral edema in gliomas [16][17][18]34]. In our series of experiments, for the first time, we clearly demonstrated that PBM stimulates BD in both healthy rodents and rats with glioma [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 62%
“…New therapeutic strategies targeting BD and the MLV functions appear to be promising [16][17][18]. The re-discovery of MLVs prompted a re-evaluation of the mechanisms responsible for regulation of BD and the formation of cerebral edema in gliomas [16][17][18]34]. In our series of experiments, for the first time, we clearly demonstrated that PBM stimulates BD in both healthy rodents and rats with glioma [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 62%
“…TTFields-enhancing techniques such as skull remodeling (Korshoej et al 2016, Mikic et al 2021 might help to compensate for the field strength loss caused by the peritumoral edema. Beyond the stifling effects of peritumoral edema on the efficacy of AEF, the edema has other clinically-relevant implications including promoting GBM cell infiltration (Ohmura et al 2023), which has been found to be associated with GBM recurrence/progression (Qin et al 2021). Electrets are inorganic or macromolecular permanently-polarized agents that can provide endogenous electrical stimulation upon application of an external electric field (Grier 2001, Zhang et al 2023, and future pre-clinical research may consider using electrets to modify the electrical properties (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some current studies have highlighted the regulatory function of AQPs on brain volume in many other neurological diseases besides tumors ( Sun et al, 2022 ; Ohmura et al, 2023 ). In gliomas, both AQP1 and AQP4, when suppressed, offer a better prognosis for patients affected by these types of tumors by edema reduction ( Faraj et al, 2022 ; Ohmura et al, 2023 ), facilitating the management of neurological deficits in the pre-and postoperative periods, with peritumoral edema being more relevant, in terms of concerns the aggressiveness of this cancer, rather than its extent, per se ( Faraj et al, 2022 ). AQP1, for example, is upregulated in the peritumoral area, especially in the vessels surrounding reactive astrocytes in high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%